Dynamics of Legal Issues in Village Head Elections in Sampang District - Ansori, Ansori; Fajar, Mohammad Ibnu (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The implementation of village head elections in Sampang district has become an important value for the village community to determine the direction of development in the village. However, despite its strategic value, the implementation of village head elections is often characterized by various problems that can hinder the local democratic process.Purposes of the Research: The purpose of this study is to analyze the problems, solutions and impacts of problems in the elections in Sampang district.Methods of the Research: The research method is to use empirical juridical research methods with legislative approaches, concepts and cases.Results Main Findings of the Research: The results of this study are that there are problems in the election of village heads in Sampang Regency, namely changes in the law on villages, the complexity of local political competition, lack of finance and logistics, the practice of money politics, lack of community participation, weak security and order and the existence of a legal vacuum in resolving disputes over the results of village head elections, these problems have an impact on the lack of public confidence in the election of village heads.